KONTROWERSJE WOKÓŁ PROBLEMÓW PODZIAŁU - Szopa, Bogumiła (Wydział Prawa i Administracji UAM, 2005)
In the context of the „Asian Miracle”, the end of the 20th century witnessed a revolution in income distribution, which consequently brought about verification of the rather widely recognised and accepted relationship: effectiveness or equality. At the same time it raised (and not only among economists) an increased interest in income distribution, emphasising the role of social stability in the processes of economic transformation. This, in turn, has led to a new perception of the economic and social phenomena, including the impact of the state policy.
CONTROVERSIES OVER THE DIVISIONAL PROPORTIONS